Motivations of electronic word-of-mouth (eWOM) sharing in the automotive customer’s journey with an analysis of consumer sentiment in Singapore - Guo, Zhiwei (2020)
Given the high cost of owning a car, many dealerships in Singapore look toward enhancing the consumer experience to make themselves stand out and gain a competitive advantage. In order to improve a customer’s ownership journey, understanding the various pain points from the perspective of the customer is crucial, as this will affect the customer’s repurchase intention and the spread of Word-Of-Mouth (WOM) either to their friends or relatives or through online channels.